La Roy Sunderland correspondence - Sunderland, La Roy, 1802-1885.
ALS (New York) from Sunderland addressed to Francis Wright primarily concerning the Wesleyan movement in the Methodist Episcopal Church.
Abolitionist, author, Methodist clergyman until 1842, and later a proponent of atheism.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Wright, Francis, -- active 1843 -- Correspondence; Methodist Episcopal Church; Wesleyan Methodist Connection of America; Abolitionists; Authors; Clergy